2017
DOI: 10.14236/ewic/hci2017.6
|View full text |Cite
|
Sign up to set email alerts
|

Presenting and visualizing image results for professional image searchers: A field evaluation

Abstract: Creative professionals such as journalists and copywriters are an important group of users who need to search for images as part of their work task. We describe the design and evaluation of a 'high density' image search interface targeted at this user group. We use a field evaluation together with a qualitative approach with creative professionals to gather feedback on the high density interface design. Our results show that creative professional viewed the interface favourably because they were able to get a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…the ability to pan and zoom images as suggested in section 6. We report this work in the same volume (Göker et al, 2017). A further area of fruitful research would be to examine cultural differences for example many Asian languages are pictorial in character (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…the ability to pan and zoom images as suggested in section 6. We report this work in the same volume (Göker et al, 2017). A further area of fruitful research would be to examine cultural differences for example many Asian languages are pictorial in character (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers working in the first of these areas have identified that Google or Google Image were the most frequently used tools to search for images among college students (Yoon, 2011). Some researchers worked on designing a high-density image search interface for creative professionals, such as journalists and copywriters (Göker et al , 2016). There are three types of user intentions – including explore/learn, entertain, and locate/acquire – dealing with image search behaviour (Xie et al , 2018).…”
Section: Literature Reviewmentioning
confidence: 99%